Assessing the Conservation Priority of Alpine Carabid Beetle Communities by Mapping the Index of Natural Value (INV) in Natura 2000 Habitats in the Brenta Dolomites (Italian Alps) - Emiliano Peretti; Marco Armanini; Roberta Chirichella; Andrea Mustoni; Mauro Gobbi (Insects)
The Dolomites (European Alps) are a UNESCO World Heritage Site known to harbor distinctive communities of carabid beetles adapted to high-altitude environments, whose composition is shaped mainly by landform and habitat type. We aimed to assess the conservation priority of carabid beetle communities in the Brenta mountain group (Italy). We used the Index of Natural Value (INV), based on the relative frequencies and abundances of highly specialized Alpine species, as a proxy of the sensitivity to disturbance, and, thus, to the vulnerability of the carabid beetle communities to extinction. We used information on Natura 2000 habitat cover to produce a map for identifying areas of the Brenta Dolomites inhabited by the carabid beetle communities most relevant for conservation. We also report on the main differences in terms of species composition between the investigated communities. We found a positive correlation between vulnerability and altitude. Specifically, the most vulnerable communities were recorded in high-altitude habitat types (limestone cliffs and pavements, calcareous and calcschist screes, and alpine calcareous grasslands). Alkaline fens resulted in having the least vulnerable community, while those in all other habitats (bush and forests) were found to have intermediate levels of vulnerability.